A study for implementation of e-maintenance for mechanical building services equipments using iSCADA system / Azmi Mohamed - Mohamed, Azmi (2003)
Routine and repetitive works may in time cause delays, which are sometimes mistakenly perceived as common matter. Tedious and time-consuming manual reports may contain inaccurate information, which is crucial for management. In realization of this matter, new methods are developed and one of the approaches is through Internet-based Supervisory Control and Data Acquisition (iSCADA). For this project, a simulation has been designed to realize the system of Internet-based Supervisory Control and Data Acquisition (iSCADA). The simulation is a small-scale model designed to replicate the real application of e-maintenance system. The simulation is based on monitoring the status of central air conditioning system in PTAR1. Before the project was started, the status of the building services equipments in PTAR1 has been identified. The simulation shows that e-maintenance is capable to monitor and report the status of building services equipments. The result of the simulation also shows that by implementing the system, user can improve the efficiency in maintenance work, thus increasing the performance.